2022
DOI: 10.1186/s42836-022-00145-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the application of deep learning methods based on convolutional network to the pathological diagnosis of PJI

Abstract: Objective This study aimed to establish a deep learning method based on convolutional networks for the preliminary study of the pathological diagnosis of prosthetic joint infections (PJI). Methods We enrolled 20 revision patients after joint replacement from the Department of Orthopedics, the First Medical Center, General Hospital of the People's Liberation Army, from January 2021 to January 2022 (10 of whom were confirmed to be infected against 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Full texts were obtained and reviewed for the remaining 16 studies. Five studies were removed, with 11 studies included for the final analysis [ 7 , 8 , 13 21 ]. The included studies targeted four areas of ML application: PJI prediction, diagnosis, antibiotic application, and prognosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full texts were obtained and reviewed for the remaining 16 studies. Five studies were removed, with 11 studies included for the final analysis [ 7 , 8 , 13 21 ]. The included studies targeted four areas of ML application: PJI prediction, diagnosis, antibiotic application, and prognosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] Periprosthetic joint infection prediction via machine learning: comprehensible personalized decision support for diagnosis The Journal of Arthroplasty 2021 323 patients Tao, Y. [ 13 ] A preliminary study on the application of deep learning methods based on convolutional network to the pathological diagnosis of periprosthetic joint infection Arthroplasty 2022 20 patients (Training sets: 461 positive images, 461 negative images) Prognosis Shohat, N. [ 20 ] 2020 Frank Stinchfield Award: identifying who will fail following irrigation and debridement for prosthetic joint infection The Bone & Joint Journal 2020 609 patients Klemt, C. [ 21 ] Machine learning models accurately predict recurrent infection following revision total knee arthroplasty for periprosthetic joint infection Knee Surgery, Sports Traumatology, Arthroscopy 2021 618 patients …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior research on intelligent pathological diagnosis of PJI showed that excessively large training patches could lead to imprecise identi cation of minute neutrophils [25]. To achieve better diagnostic results with deep learning networks, we reduced ve or more neutrophils, as speci ed in the current criterion, to two or more neutrophils, with pixel area correspondingly lowered from 1200 × 1800 pixels to 600 × 600 pixels.…”
Section: Establishment Of Image Datasetmentioning
confidence: 99%
“…Following the 2018 ICM guidelines, we simpli ed the problem by using "at least 5 neutrophils in high-power elds within pathological slides" as the diagnostic criterion. Patches meeting the PJI diagnostic criteria were selected and utilized to train a supervised learning model based on ResNet34, resulting in an intelligent model for PJI image-level diagnosis [25]. The aforementioned ResNet model has been widely applied for the intelligent recognition of images and pathological pictures [39], yielding high accuracy in the pathological diagnosis of malignancies such as lung cancer, gastric cancer, breast cancer, and bladder cancer [40][41][42][43].…”
Section: The Application Of Arti Cial Intelligence In Image Recogniti...mentioning
confidence: 99%